Proposal of Parashewanella gen. nov. to accommodate Parashewanella curva sp. nov. and Parashewanella spongiae comb. nov. in the Shewanellaceae. Issue 5 (20th February 2019) - Xu, Shuailiang; Yu, Kefu; Su, Hongfei; Chen, Biao; Huang, Wen; Liang, Jiayuan; Wang, Yinghui; Wang, Guanghua
Abstract : A Gram-stain-negative, non-spore-forming, motile, aerobic, curved rod shaped bacterium, designed strain C51 T, was isolated from coral (genus Porites ) sampled at Weizhou Island, China. The optimal growth occurred in 2-3 % NaCl (w/v), at 25 °C and pH 8. Phylogenetic analyses based on the 16S rRNA gene, the gyrB gene and the Up-to-date Bacterial Core Gene set (92 genes) indicated that strain C51 T forms a stable cluster with Shewanella spongiae KCTC 22492 T, and had 94 % 16S rRNA gene similarity to its closest type strain S. spongiae KCTC 22492 T . The only detected respiratory quinone was Q-8 and it could not produce menaquinone. The genome DNA G+C content was 40.1 mol%. The major cellular fatty acids were iso-C11:0 3-OH, iso-C15:0, C16:0, C16:1 ω7 c /ω6 c, C18:0 and iso-C13:0 3-OH. The major polar lipids were phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol, three unidentified aminolipids and three unidentified polar lipids. Its low genome DNA G+C content, lack of an aminolipid and a difference in its substrate oxidation ability indicated that strain C51 T should represent a new species. Furthermore, its distinct phylogeny, Shewanella- specific FISH probe SHEW227 mismatch, lower cellular G+C content and inability to produce menaquinones indicated that the C51 T clade should represent a new genus in the Shewanellaceae, for which the name Parashewanella gen. nov. is proposed, the type species is Parashewanella spongiae comb. nov., and another species is Parashewanella curva sp. nov. The type strains of Parashewanella spongiae and Parashewanella curva are HJ039 T (=KCTC 22492 T =KCCM 42304 T =JCM 13830 T ) and C51 T (=MCCC 1K03463 T =KCTC 62318 T ), respectively.